Soil heavy metal pollution repairing agent based on biomass power plant ash and preparation method thereof
Through the design of surface-modified porous biomass power plant ash cluster and polymer-modified bentonite, combined with soil modification repair agents, the stability and adsorption performance of soil heavy metal pollution repair agents in the prior art in different environments is solved. The problem has achieved efficient and lasting repair effect of heavy metal pollution.
Patent Information
- Application Number
- CN202411583330.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-14
AI Technical Summary
Existing soil heavy metal pollution repair agents based on biomass power plant ash have been exposed to a wet or acidic environment for a long time, resulting in weakening of the repair effect and chemical reaction with other components in the soil. New by-products may be formed, increasing the ecological risks of the soil.
By designing surface-modified porous biomass power plant ash cluster, surface modification is carried out using γ-aminopropyltriethoxysilane and humic acid to enhance the mechanical stability and chemical adsorption capacity of the material, and combined with polymer modification. Bentonite and soil modification repair agents improve the adsorption performance and stability of repair agents.
It significantly improves the adsorption efficiency, stability and sustainability of soil heavy metal pollution repair agents, extends its service life, ensures its adaptability and broad-spectrum adsorption capacity in different environments, and effectively inhibits the migration and bioeffectiveness of heavy metals. .
Smart Images

Figure CN119432394A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a soil heavy metal pollution repair agent based on biomass power plant ash, and in particular to a soil heavy metal pollution repair agent based on biomass power plant ash and a preparation method thereof. Background Art
[0002] Heavy metal pollution in soil is a widespread ecological and environmental problem worldwide, especially in industrialized and mineral-rich areas. Whether it is agricultural land or urban green space, heavy metal pollution in soil will have long-term and irreversible effects on plants, animals and even human health. Therefore, improving and repairing heavy metal-contaminated soil has become one of the key issues that need to be urgently addressed in current environmental governance. Existing remediation methods include physical remediation, chemical remediation and biological remediation, but among them, chemical adsorption and fixation-based remediation agent technology has gradually become the mainstream development direction due to its convenience and efficiency. In this context, it is particularly important to develop soil remediation agents with high adsorption capacity, low environmental risk and economic feasibility. The remediation agent based on biomass power plant ash has become a material with great potential because of its wide source, low cost and porous structure. It can effectively adsorb and fix heavy metal ions, reduce their mobility and bioavailability. However, to achieve the widespread promotion of this application, the remediation agent not only needs to have excellent adsorption performance, but also needs to meet the long-term stability in complex environments to ensure that it can maintain a continuous remediation effect under different soil types, humidity and temperature changes. Therefore, in practical applications, developing soil remediation agents with high adsorption efficiency, good environmental stability and low cost can not only significantly improve the effect of soil remediation, but also provide technical support for large-scale soil remediation projects, thereby promoting the progress of the entire environmental protection industry.
[0003] Although biomass power plant ash shows good application prospects in the field of soil heavy metal remediation, the current related technologies still have some shortcomings. For example, the Chinese patent with publication number CN117821078A discloses a soil conditioner based on biomass power plant ash and its preparation method. Although the pore structure design of the material improves the adsorption capacity, the stability of the pore structure and the adsorption performance will gradually decrease after long-term exposure to a wet or acidic environment, resulting in a weakened remediation effect. Furthermore, when existing remediation agents react chemically with other components in the soil, new by-products may be formed, increasing the ecological risks of the soil. Therefore, although the existing technology has made certain progress in some aspects, how to improve the adaptability of the remediation agent in different environments, extend its service life, and ensure its broad-spectrum adsorption capacity for a variety of heavy metal pollutants is still an urgent problem to be solved in the current research field. Summary of the invention
[0004] (1) Technical issues solved
[0005] The purpose of the present invention is to provide a soil heavy metal pollution remediation agent based on biomass power plant ash and a preparation method thereof, so as to solve the problem that the current soil heavy metal pollution remediation agent has insufficient improvement and repair effect on soil heavy metal pollution.
[0006] (2) Technical solution
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] The soil heavy metal pollution remediation agent based on biomass power plant ash includes the following components in parts by weight: 30 to 45 parts of surface modified porous biomass power plant ash, 4.5 to 9.0 parts of polymer modified bentonite, 3 to 7 parts of soil modification remediation agent, and 1.5 to 4.5 parts of clay mineral;
[0009] The surface-modified porous biomass power plant ash is prepared from γ-aminopropyltriethoxysilane and humic acid surface-modified porous biomass power plant ash clusters;
[0010] The porous biomass power plant ash clusters are obtained by freezing the biomass power plant ash with liquid nitrogen, freeze drying, grinding and screening;
[0011] The polymer modified bentonite is obtained by modifying bentonite through polymerization reaction of acrylic acid and sodium carboxymethyl cellulose monomers;
[0012] The average diameter of the porous biomass power plant ash clusters is 100 to 200 μm;
[0013] The specific surface area of the porous biomass power plant ash is 300 to 500 m 2 / g;
[0014] The porous structure of the porous biomass power plant ash is a fishbone structure, and the porous pore spacing is 1.0 to 3.5 μm.
[0015] Furthermore, the preparation method of the surface modified porous biomass power plant ash is as follows: by weight, 20 to 35 parts of porous biomass power plant ash clusters, 2.0 to 5.0 parts of γ-aminopropyltriethoxysilane, 1.0 to 3.0 parts of humic acid and 100 to 150 parts of ethanol are added to a container, stirred at room temperature at a speed of 200 to 400 rpm for 120 to 360 minutes, then filtered and retained the filter residue, and the filter residue was completely vacuum dried at room temperature to obtain the surface modified porous biomass power plant ash.
[0016] Furthermore, the preparation method of the porous biomass power plant ash clusters is as follows: in parts by weight, the biomass power plant ash is sequentially washed, crushed, sieved and dried to obtain pretreated biomass power plant ash, 10 to 25 parts of pretreated biomass power plant ash, 1.0 to 2.5 parts of glucose, 2.0 to 5 parts of clay minerals and 100 parts of water are mixed evenly and added to a columnar glass tube, which is then vertically immersed in liquid nitrogen for freezing, and after the ice crystal front converges from the outside to the inside center of the columnar glass tube, it is then completely dried by freeze drying, and then the freeze-dried glucose-biomass power plant ash complex in the columnar glass tube is taken out, and then placed in a tubular furnace to be cracked at a temperature of 600 to 800° C. for 120 to 240 minutes under a nitrogen atmosphere, and after cooling to room temperature, the sample is lightly ground and sieved to obtain a porous biomass power plant ash cluster.
[0017] Furthermore, the freezing temperature of the liquid nitrogen is -50 to -80°C, and the freezing rate is 6 to 10°C / min.
[0018] The present invention adopts the design of surface-modified porous biomass power plant ash clusters mainly to improve the heavy metal pollution remediation performance of soil. Through the refined structural design and surface chemical modification of porous biomass power plant ash clusters, the present invention aims to significantly improve its adsorption capacity, stability and long-term effect on heavy metal ions in the soil, so as to effectively inhibit the mobility and bioavailability of heavy metals and achieve the effect of lasting soil remediation. First, biomass power plant ash is used as the main raw material, and a series of pretreatment steps such as washing, crushing, screening and drying are performed to obtain pretreated biomass power plant ash with uniform particle size. The porous structure is constructed by freeze-drying, and the freezing temperature is controlled between -50 and -80°C, and the freezing rate is 6 to 10°C / minute. This process forms a fishbone-shaped porous structure by regulating the growth of ice crystals. The fishbone-shaped structure has a good pore distribution, and the pore spacing is between 1.0 and 3.5μm. This structure not only greatly increases the specific surface area of the material (up to 300 to 500m 2 / g), and also provides more physical channels for the transmission and adsorption of heavy metal ions. After freeze-drying, the porous structure is further stabilized through a cracking process at 600 to 800°C, and the mechanical strength and durability of the material are ensured. In the surface modification process, the present invention selects γ-aminopropyltriethoxysilane and humic acid as the main modifiers. γ-aminopropyltriethoxysilane reacts with silicates and aluminates in the ash of biomass power plants through a silane coupling reaction to form an organic-inorganic composite material. This composite material not only enhances the mechanical stability of the material, but also improves the complexation between clusters and heavy metal ions through the introduction of functional groups such as amino groups. Humic acid, as a natural organic polymer material, is rich in various functional groups such as carboxyl and hydroxyl groups. It can form stable complexes with heavy metal ions through complexation, chelation and ion exchange, thereby further enhancing the adsorption capacity and stability of the material. In addition, glucose is used as a template before freeze drying to form a complex with biomass power plant ash and clay minerals. After freeze drying and cracking, glucose is removed, leaving an optimized pore structure. This process significantly improves the porosity of the material and provides ample space for the diffusion and adsorption of heavy metal ions in the material. The addition of clay minerals also plays an important role. Its own high cation exchange capacity further improves the adsorption capacity of the material, while improving the dispersibility of the material and enhancing its application effect in actual soil remediation. The average diameter of the porous biomass power plant ash clusters is controlled between 100 and 200 μm. This range ensures the operability and dispersibility of the material in the soil, and helps to improve its adsorption efficiency in practical applications. Through the synergistic effect of each component, the porous biomass power plant ash clusters designed by the present invention show significant improvements in specific surface area, porosity, chemical stability and adsorption capacity, and can effectively capture and fix heavy metal ions in the soil. In summary, the present invention finely controls the structure and surface chemical properties of porous biomass power plant ash clusters, and utilizes the synergistic effect of freeze drying and surface modification technology to make the material have excellent heavy metal adsorption performance. The porous structure provides sufficient physical adsorption sites, and the surface chemical modification enhances the chemical adsorption capacity of the material for heavy metal ions through mechanisms such as complexation and ion exchange.
[0019] Furthermore, the preparation method of the polymer modified bentonite is as follows: by weight, 50 to 75 parts of bentonite, 2.4 to 5.4 parts of acrylic acid, 1.5 to 4.5 parts of sodium carbonate and 100 parts of water are added into a reaction kettle and stirred at a stirring speed of 100 to 200 rpm for 30 to 45 minutes, then 0.4 to 0.9 parts of sodium carboxymethyl cellulose are added, and then the solution is heated to 70 to 80° C., 1.0 to 3.5 parts of N,N'-methylenebisacrylamide and 0.2 to 0.8 parts of potassium persulfate are added and continued to stir for 60 to 120 minutes to cause a polymerization reaction, after the reaction is completed, the solution is filtered to retain the filter residue, and then the filter residue is washed with deionized water for 3 times, and finally vacuum dried at room temperature to constant weight to obtain the polymer modified bentonite.
[0020] Furthermore, the mass ratio of the acrylic acid to sodium carboxymethyl cellulose is 6:1.
[0021] The present invention adopts the design of polymer-modified bentonite, which is mainly used to enhance the adsorption performance of soil heavy metal pollution remediation agents. By compounding bentonite with acrylic acid and sodium carboxymethyl cellulose in a specific ratio for polymer modification, the selective adsorption capacity of bentonite for heavy metal ions is significantly improved. Specifically, the synergistic effect of acrylic acid and sodium carboxymethyl cellulose not only enhances the adsorption capacity of bentonite for heavy metal ions, but also optimizes its adsorption mechanism. At low concentrations of metal ions, the polymer coating on the surface of the modified bentonite can effectively bind to Pb through electrostatic action and chelation. 2+ and Cd 2 + Ion binding, thereby delaying the exchange of multivalent cations with low-valent exchangeable cations (such as Na + , K + At high concentrations of metal ions, the highly absorbent polymer added to the modified bentonite forms a gel structure, which further enhances the adsorption capacity of heavy metal ions. By blocking pore channels and increasing adsorption sites, the adsorption of Pb in medium and high concentration solutions is achieved. 2+ and Cd 2+ Therefore, the polymer-modified bentonite of the present invention can provide an efficient and selective heavy metal ion removal effect in the remediation of soil heavy metal pollution, ensuring the safety and effectiveness of the remediation process.
[0022] Furthermore, the soil modifying and repairing agent is a mixture of phosphate and limestone in a mass ratio of (2-3):1.
[0023] Furthermore, the phosphate is any one of tricalcium phosphate, monocalcium phosphate, dicalcium phosphate or ferric phosphate.
[0024] Furthermore, the clay mineral is a mixture of montmorillonite, attapulgite, zeolite and vermiculite in a mass ratio of 4:2:2.5:1.5.
[0025] The phosphate and limestone in the soil modification and remediation agent are mixed in a mass ratio of (2-3):1, aiming to repair the heavy metal contaminated soil through the dual effects of chemical precipitation and pH adjustment. Phosphates (including tricalcium phosphate, monocalcium phosphate, dicalcium phosphate or iron phosphate) can react with heavy metal ions to form insoluble phosphate precipitates, thereby reducing the bioavailability and mobility of heavy metals. Limestone enhances the reaction efficiency of phosphates and heavy metals by adjusting the pH value of the soil, while improving the buffering capacity of the soil. The selection of clay minerals further enhances the heavy metal adsorption capacity of the remediation agent. Montmorillonite, attapulgite, zeolite and vermiculite are mixed in a ratio of 4:2:2.5:1.5, providing abundant surface active sites and high cation exchange capacity, effectively fixing heavy metal ions and increasing the overall stability and adsorption performance of the remediation agent.
[0026] The present invention also provides a method for preparing a soil heavy metal pollution repair agent based on biomass power plant ash, comprising the following steps:
[0027] S1. Pretreatment of biomass power plant ash: washing, crushing, drying and sieving the biomass power plant ash in sequence to obtain pretreated biomass power plant ash with an average particle size of 300 to 500 nm;
[0028] S2. Preparation of surface-modified porous biomass power plant ash: The pretreated biomass power plant ash obtained in S1 is sequentially subjected to liquid nitrogen freezing and freeze-drying, and then ground and sifted to obtain porous biomass power plant ash clusters, and then the porous biomass power plant ash clusters are surface-modified by γ-aminopropyltriethoxysilane and humic acid to obtain surface-modified porous biomass power plant ash.
[0029] S3. Forming of soil heavy metal pollution remediation agent: Add surface modified porous biomass power plant ash, polymer modified bentonite, soil modification remediation agent and clay mineral into a mixer according to weight proportions, mix evenly, and then form into any one of spherical, cylindrical or rod shapes through a double-roll extrusion granulator. The parameters of the double-roll extrusion granulator are as follows: roller diameter of 150-300mm; roller speed of 25-50rpm; extrusion pressure of 10-50 MPa; particle diameter of 3-10mm; mold aperture of 0.5-5mm; power of 7.5-22 kilowatts. Finally, dry in an infrared dryer and package for storage.
[0030] (3) Beneficial technical effects
[0031] 1. The present invention significantly improves the remediation effect of heavy metal contaminated soil through the design of surface-modified porous biomass power plant ash clusters. Compared with the prior art, the present invention has obvious advantages in adsorption efficiency, stability and sustainability, especially in terms of specific surface area, porosity and chemical adsorption capacity. The porous biomass power plant ash is constructed into a fishbone-shaped porous structure through freeze-drying and cracking processes, which significantly increases the physical adsorption sites. At the same time, γ-aminopropyltriethoxysilane and humic acid are introduced for surface modification to enhance the complexation and chelation of heavy metal ions. Compared with traditional materials, the repair agent of the present invention has more efficient adsorption performance and longer service life. It is particularly suitable for complex heavy metal pollution scenes and can effectively solve the heavy metal mobility and bioavailability problems that have long plagued the industry. Through the synergistic effect between components, the porous structure of biomass power plant ash works together with clay minerals and modifiers to ensure the excellent performance of the material in different environments, and has significant application prospects and industry driving force.
[0032] 2. The present invention significantly improves the adsorption performance of soil heavy metal pollution remediation agents through the design of polymer-modified bentonite. Compared with the prior art, the present invention has obvious advantages in adsorption efficiency, selectivity and adaptability. By composite-modifying bentonite with acrylic acid and sodium carboxymethyl cellulose, the selective adsorption capacity of heavy metal ions is enhanced, especially at low concentrations of metal ions. The polymer coating effectively binds Pb through electrostatic action and chelation. 2+ and Cd 2+ , and at high concentrations of metal ions, the formed gel structure further increases the adsorption sites, ensuring efficient removal effects under different concentration conditions. The present invention shows excellent heavy metal removal effects in severely polluted agricultural land and industrial wasteland, solves the problem of low efficiency in the exchange of multivalent cations and bentonite in the prior art, and has significant environmental friendliness and cost advantages. Through the synergistic effect of each component, acrylic acid and sodium carboxymethyl cellulose optimize the adsorption performance of bentonite, and the selection of ratio and process ensures the high efficiency and stability of the repair agent, showing broad application prospects.
[0033] 3. The soil modification and repair agent of the present invention realizes efficient repair of heavy metal contaminated soil by combining phosphate and limestone in a mass ratio of (2-3):1. Phosphates (such as tricalcium phosphate, monocalcium phosphate, dicalcium phosphate or iron phosphate) form insoluble precipitates with heavy metal ions, which significantly reduce the bioavailability and mobility of heavy metals. At the same time, limestone enhances the reaction efficiency of phosphates and improves the buffering capacity of soil by adjusting the pH value of the soil. Clay minerals (montmorillonite, attapulgite, zeolite and vermiculite are mixed in a ratio of 4:2:2.5:1.5) further improve the heavy metal adsorption capacity of the repair agent. Its high cation exchange capacity and rich surface active sites can effectively fix heavy metal ions and ensure the stability and durability of the repair agent in complex soil environments. The synergistic effect of each component not only improves the repair effect, but also enhances the environmental buffering capacity of the soil, making the repair agent have significant application value in the treatment of heavy metal pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a SEM morphology image of the original biomass power plant ash used in Example 1 of the present invention.
[0035] Figure 2 This is a SEM morphology image of the surface modified porous biomass power plant ash prepared in Example 1 of the present invention.
[0036] Figure 3 The infrared Fourier spectra of the bentonite and polymer-modified bentonite prepared in Example 1 of the present invention are shown. DETAILED DESCRIPTION
[0037] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0038] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.
[0039] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies
[0040]
[0041]
[0042] Example 1
[0043] The soil heavy metal pollution remediation agent based on biomass power plant ash includes the following components by weight: 30 parts of surface modified porous biomass power plant ash, 4.5 parts of polymer modified bentonite, 3 parts of soil modification remediation agent, and 1.5 parts of clay mineral;
[0044] The surface-modified porous biomass power plant ash of this embodiment is prepared by surface-modified porous biomass power plant ash clusters with γ-aminopropyltriethoxysilane and humic acid; the porous biomass power plant ash clusters are obtained by liquid nitrogen freezing, freeze drying and grinding and screening the biomass power plant ash; the polymer-modified bentonite is obtained by modifying bentonite with acrylic acid and sodium carboxymethyl cellulose monomers through polymerization reaction.
[0045] The average diameter of the porous biomass power plant ash clusters in this embodiment is 100 μm; the specific surface area of the porous biomass power plant ash is 300 m 2 / g; the porous structure of the porous biomass power plant ash is a fishbone structure; the porous pore spacing is 1.0μm.
[0046] The preparation method of the surface modified porous biomass power plant ash of this embodiment is as follows: 20 parts of porous biomass power plant ash clusters, 2.0 parts of γ-aminopropyltriethoxysilane, 1.0 parts of humic acid and 100 parts of ethanol are added into a container by weight, stirred at room temperature at a speed of 200 rpm for 120 minutes, and then filtered to retain the filter residue, and the filter residue is completely vacuum dried at room temperature to obtain the surface modified porous biomass power plant ash. The preparation method of porous biomass power plant ash clusters is as follows: by weight, the biomass power plant ash is sequentially washed, crushed, sieved and dried to obtain pretreated biomass power plant ash, 10 parts of pretreated biomass power plant ash, 1.0 parts of glucose, 2.0 parts of clay minerals and 100 parts of water are mixed evenly and added to a cylindrical glass tube, and then vertically immersed in liquid nitrogen for liquid nitrogen freezing, after the ice crystal front converges from the outside to the inside center of the cylindrical glass tube, it is then completely dried by freeze drying, and then the freeze-dried glucose-biomass power plant ash complex in the cylindrical glass tube is taken out, and then it is placed in a tubular furnace to be cracked at a temperature of 600°C for 120 minutes under a nitrogen atmosphere, and after cooling to room temperature, the sample is slightly ground and sieved to obtain porous biomass power plant ash clusters. The liquid nitrogen freezing temperature is -80°C, and the freezing rate is 6°C / min.
[0047] The preparation method of the polymer-modified bentonite of the present embodiment is as follows: by weight, 50 parts of bentonite, 2.4 parts of acrylic acid, 1.5 parts of sodium carbonate and 100 parts of water are added into a reaction kettle and stirred at a stirring speed of 100 rpm for 30 minutes, then 0.4 parts of sodium carboxymethyl cellulose are added, and then the solution is heated to 70° C., 1.0 parts of N,N'-methylenebisacrylamide and 0.2 parts of potassium persulfate are added and stirred for 60 minutes to cause a polymerization reaction, after the reaction is completed, the solution is filtered to retain the filter residue, and then the filter residue is washed with deionized water for 3 times, and finally vacuum dried at room temperature to constant weight to obtain the polymer-modified bentonite.
[0048] The soil modification and repair agent of this embodiment is a mixture of tricalcium phosphate and limestone in a mass ratio of 2:1. The clay minerals are a mixture of montmorillonite, attapulgite, zeolite and vermiculite in a mass ratio of 4:2:2.5:1.5.
[0049] The preparation method of the soil heavy metal pollution remediation agent based on biomass power plant ash of this embodiment comprises the following steps:
[0050] S1. Pretreatment of biomass power plant ash: The biomass power plant ash is sequentially washed, crushed, dried and sieved to obtain pretreated biomass power plant ash with an average particle size of 300 nm;
[0051] S2. Preparation of surface-modified porous biomass power plant ash: The pretreated biomass power plant ash obtained in S1 is sequentially subjected to liquid nitrogen freezing and freeze drying, followed by grinding and sieving to obtain porous biomass power plant ash clusters, and then the porous biomass power plant ash clusters are surface-modified by γ-aminopropyltriethoxysilane and humic acid to obtain surface-modified porous biomass power plant ash;
[0052] S3. Forming of soil heavy metal pollution remediation agent: Add surface modified porous biomass power plant ash, polymer modified bentonite, soil modification remediation agent and clay mineral into a mixer according to weight proportions, mix evenly, and then form into spherical, cylindrical or rod shapes through a double-roll extrusion granulator. The parameters of the double-roll extrusion granulator are as follows: roller diameter is 150mm; roller speed is 25rpm; extrusion pressure is 10 MPa; particle diameter is 3mm; mold aperture is 0.5mm; power is 7.5 kilowatts, and finally dried through an infrared dryer and packaged for storage.
[0053] By analyzing the test results of Example 1 of the present invention, the following conclusions are obtained: Figure 1 shows the SEM morphology of the original biomass power plant ash, indicating that its particle structure presents an irregular morphology; Figure 2The SEM morphology of the surface-modified porous biomass power plant ash is shown, proving that it has formed a significant fishbone-like porous structure, which helps to increase the specific surface area and adsorption performance of the material. Figure 3 The infrared Fourier transform spectra (FTIR) of bentonite and polymer-modified bentonite show that compared with the unprocessed bentonite, the polymer-modified bentonite has additional characteristic peaks at 2940cm-1 (asymmetric stretching of methyl), 1563cm-1 and 1416cm-1 (symmetric stretching of carboxyl and carbon-oxygen double bonds, respectively) in its FTIR spectrum. These changes indicate that the polymer has successfully introduced functional groups and significantly improved the structure and chemical properties of bentonite.
[0054] Example 2
[0055] The soil heavy metal pollution remediation agent based on biomass power plant ash includes the following components in parts by weight: 34 parts of surface modified porous biomass power plant ash, 6.3 parts of polymer modified bentonite, 4.2 parts of soil modification remediation agent, and 2.4 parts of clay mineral.
[0056] The surface-modified porous biomass power plant ash of this embodiment is prepared by surface-modified porous biomass power plant ash clusters with γ-aminopropyltriethoxysilane and humic acid; the porous biomass power plant ash clusters are obtained by liquid nitrogen freezing, freeze drying and grinding and screening the biomass power plant ash; the polymer-modified bentonite is obtained by modifying bentonite with acrylic acid and sodium carboxymethyl cellulose monomers through polymerization reaction.
[0057] The average diameter of the porous biomass power plant ash clusters in this embodiment is 130 μm; the specific surface area of the porous biomass power plant ash is 360 m 2 / g; the porous structure of the porous biomass power plant ash is a fishbone structure; the porous pore spacing is 1.8μm.
[0058] The preparation method of the surface modified porous biomass power plant ash of this embodiment is as follows: 23 parts of porous biomass power plant ash clusters, 3.0 parts of γ-aminopropyltriethoxysilane, 1.6 parts of humic acid and 115 parts of ethanol are added into a container by weight, stirred at room temperature at a speed of 260 rpm for 168 minutes, and then filtered to retain the filter residue, and the filter residue is completely vacuum dried at room temperature to obtain the surface modified porous biomass power plant ash. The preparation method of porous biomass power plant ash clusters is as follows: by weight, the biomass power plant ash is sequentially washed, crushed, sieved and dried to obtain pretreated biomass power plant ash, 13 parts of pretreated biomass power plant ash, 1.5 parts of glucose, 3.0 parts of clay minerals and 100 parts of water are mixed evenly and added to a cylindrical glass tube, and then vertically immersed in liquid nitrogen for liquid nitrogen freezing, after the ice crystal front converges from the outside to the inside center of the cylindrical glass tube, it is then completely dried by freeze drying, and then the freeze-dried glucose-biomass power plant ash complex in the cylindrical glass tube is taken out, and then it is placed in a tubular furnace to be cracked at a temperature of 720°C for 192 minutes under a nitrogen atmosphere, and after cooling to room temperature, the sample is slightly ground and sieved to obtain porous biomass power plant ash clusters. The liquid nitrogen freezing temperature is -71°C, and the freezing rate is 8°C / min.
[0059] The preparation method of the polymer modified bentonite of this embodiment is as follows: by weight, 58 parts of bentonite, 3.6 parts of acrylic acid, 2.1 parts of sodium carbonate and 100 parts of water are added into a reaction kettle and stirred at a stirring speed of 130 rpm for 38 minutes, then 0.6 parts of sodium carboxymethyl cellulose is added, and then the solution is heated to 74°C, 2.1 parts of N,N'-methylenebisacrylamide and 0.4 parts of potassium persulfate are added and stirred for 84 minutes to cause a polymerization reaction, after the reaction is completed, the solution is filtered to retain the filter residue, and then the filter residue is washed with deionized water for 3 times, and finally vacuum dried at room temperature to constant weight to obtain the polymer modified bentonite.
[0060] The soil modification and repair agent of this embodiment is a mixture of monocalcium phosphate and limestone in a mass ratio of 2.3:1. The clay minerals are a mixture of montmorillonite, attapulgite, zeolite and vermiculite in a mass ratio of 4:2:2.5:1.5.
[0061] The preparation method of the soil heavy metal pollution remediation agent based on biomass power plant ash of this embodiment comprises the following steps:
[0062] S1. Pretreatment of biomass power plant ash: The biomass power plant ash is sequentially washed, crushed, dried and sieved to obtain pretreated biomass power plant ash with an average particle size of 360 nm;
[0063] S2. Preparation of surface-modified porous biomass power plant ash: The pretreated biomass power plant ash obtained in S1 is sequentially subjected to liquid nitrogen freezing and freeze drying, followed by grinding and sieving to obtain porous biomass power plant ash clusters, and then the porous biomass power plant ash clusters are surface-modified by γ-aminopropyltriethoxysilane and humic acid to obtain surface-modified porous biomass power plant ash;
[0064] S3. Forming of soil heavy metal pollution remediation agent: Add surface modified porous biomass power plant ash, polymer modified bentonite, soil modification remediation agent and clay mineral into a mixer according to weight proportions, mix evenly, and then form into spherical, cylindrical or rod shapes through a double-roll extrusion granulator. The parameters of the double-roll extrusion granulator are as follows: roller diameter is 195mm; roller speed is 33rpm; extrusion pressure is 22MPa; particle diameter is 5mm; mold aperture is 2mm; power is 11kW, and finally dried through an infrared dryer and packaged for storage.
[0065] Example 3
[0066] The soil heavy metal pollution remediation agent based on biomass power plant ash includes the following components in parts by weight: 39 parts of surface modified porous biomass power plant ash, 7.2 parts of polymer modified bentonite, 5.4 parts of soil modification remediation agent, and 3.3 parts of clay mineral.
[0067] The surface-modified porous biomass power plant ash of this embodiment is prepared by surface-modified porous biomass power plant ash clusters with γ-aminopropyltriethoxysilane and humic acid; the porous biomass power plant ash clusters are obtained by liquid nitrogen freezing, freeze drying and grinding and screening the biomass power plant ash; the polymer-modified bentonite is obtained by modifying bentonite with acrylic acid and sodium carboxymethyl cellulose monomers through polymerization reaction.
[0068] The average diameter of the porous biomass power plant ash clusters in this embodiment is 160 μm; the specific surface area of the porous biomass power plant ash is 420 m 2 / g; the porous structure of the porous biomass power plant ash is a fishbone structure; the porous pore spacing is 2.6μm.
[0069] The preparation method of the surface modified porous biomass power plant ash in this embodiment is as follows: 29 parts of porous biomass power plant ash clusters, 3.8 parts of γ-aminopropyltriethoxysilane, 2.2 parts of humic acid and 130 parts of ethanol are added into a container by weight, stirred at room temperature at a speed of 320 rpm for 240 minutes, and then filtered to retain the filter residue, and the filter residue is completely vacuum dried at room temperature to obtain the surface modified porous biomass power plant ash. The preparation method of porous biomass power plant ash clusters is as follows: by weight, the biomass power plant ash is sequentially washed, crushed, sieved and dried to obtain pretreated biomass power plant ash, 19 parts of pretreated biomass power plant ash, 1.8 parts of glucose, 4.2 parts of clay minerals and 100 parts of water are mixed evenly and added to a cylindrical glass tube, and then vertically immersed in liquid nitrogen for liquid nitrogen freezing, after the ice crystal front converges from the outside to the center of the inside of the cylindrical glass tube, it is then completely dried by freeze drying, and then the freeze-dried glucose-biomass power plant ash complex in the cylindrical glass tube is taken out, and then it is placed in a tubular furnace to be cracked at a temperature of 720°C for 192 minutes under a nitrogen atmosphere, and after cooling to room temperature, the sample is slightly ground and sieved to obtain porous biomass power plant ash clusters. The liquid nitrogen freezing temperature is -62°C, and the freezing rate is 8°C / min.
[0070] The preparation method of the polymer modified bentonite of this embodiment is as follows: by weight, 65 parts of bentonite, 4.2 parts of acrylic acid, 3.3 parts of sodium carbonate and 100 parts of water are added to a reactor and stirred at a stirring speed of 160 rpm for 42 minutes, then 0.7 parts of sodium carboxymethyl cellulose are added, and then the solution is heated to 75°C, 2.8 parts of N,N'-methylenebisacrylamide and 0.6 parts of potassium persulfate are added and stirred for 108 minutes to cause a polymerization reaction, after the reaction is completed, the solution is filtered to retain the filter residue, and then the filter residue is washed with deionized water for 3 times, and finally vacuum dried at room temperature to constant weight to obtain polymer modified bentonite. The mass ratio of acrylic acid to sodium carboxymethyl cellulose is 6:1.
[0071] The soil modification and repair agent of this embodiment is a mixture of calcium dihydrogen phosphate and limestone in a mass ratio of 2.6: 1. The clay minerals are a mixture of montmorillonite, attapulgite, zeolite and vermiculite in a mass ratio of 4:2:2.5:1.5.
[0072] The preparation method of the soil heavy metal pollution remediation agent based on biomass power plant ash of this embodiment comprises the following steps:
[0073] S1. Pretreatment of biomass power plant ash: The biomass power plant ash is sequentially washed, crushed, dried and sieved to obtain pretreated biomass power plant ash with an average particle size of 420 nm;
[0074] S2. Preparation of surface-modified porous biomass power plant ash: The pretreated biomass power plant ash obtained in S1 is sequentially subjected to liquid nitrogen freezing and freeze drying, followed by grinding and sieving to obtain porous biomass power plant ash clusters, and then the porous biomass power plant ash clusters are surface-modified by γ-aminopropyltriethoxysilane and humic acid to obtain surface-modified porous biomass power plant ash;
[0075] S3. Forming of soil heavy metal pollution remediation agent: Add surface modified porous biomass power plant ash, polymer modified bentonite, soil modification remediation agent and clay mineral into a mixer according to weight proportions, mix evenly, and then form into spherical, cylindrical or rod shapes through a double-roll extrusion granulator. The parameters of the double-roll extrusion granulator are as follows: roller diameter is 240mm; roller speed is 40rpm; extrusion pressure is 34 MPa; particle diameter is 7mm; mold aperture is 3.5mm; power is 16 kilowatts, and finally dried through an infrared dryer and packaged for storage.
[0076] Example 4
[0077] The soil heavy metal pollution remediation agent based on biomass power plant ash includes the following components in parts by weight: 45 parts of surface modified porous biomass power plant ash, 9.0 parts of polymer modified bentonite, 7 parts of soil modification remediation agent, and 4.5 parts of clay mineral.
[0078] The surface-modified porous biomass power plant ash of this embodiment is prepared by surface-modified porous biomass power plant ash clusters with γ-aminopropyltriethoxysilane and humic acid; the porous biomass power plant ash clusters are obtained by liquid nitrogen freezing, freeze drying and grinding and screening the biomass power plant ash; the polymer-modified bentonite is obtained by modifying bentonite with acrylic acid and sodium carboxymethyl cellulose monomers through polymerization reaction.
[0079] The average diameter of the porous biomass power plant ash clusters in this embodiment is 200 μm; the specific surface area of the porous biomass power plant ash is 500 m 2 / g; the porous structure of the porous biomass power plant ash is a fishbone structure; the porous pore spacing is 3.5μm.
[0080] The preparation method of the surface modified porous biomass power plant ash of this embodiment is as follows: 35 parts of porous biomass power plant ash clusters, 5.0 parts of γ-aminopropyltriethoxysilane, 3.0 parts of humic acid and 150 parts of ethanol are added into a container by weight, stirred at room temperature at a speed of 400 rpm for 360 minutes, and then filtered to retain the filter residue, and the filter residue is completely vacuum dried at room temperature to obtain the surface modified porous biomass power plant ash. The preparation method of porous biomass power plant ash clusters is as follows: by weight, the biomass power plant ash is sequentially washed, crushed, sieved and dried to obtain pretreated biomass power plant ash, 25 parts of pretreated biomass power plant ash, 2.5 parts of glucose, 5.0 parts of clay minerals and 100 parts of water are mixed evenly and added to a cylindrical glass tube, and then vertically immersed in liquid nitrogen for liquid nitrogen freezing, after the ice crystal front converges from the outside to the inside center of the cylindrical glass tube, it is then completely dried by freeze drying, and then the freeze-dried glucose-biomass power plant ash complex in the cylindrical glass tube is taken out, and then it is placed in a tubular furnace to be cracked at a temperature of 800°C for 240 minutes under a nitrogen atmosphere, and after cooling to room temperature, the sample is slightly ground and sieved to obtain porous biomass power plant ash clusters. The liquid nitrogen freezing temperature is -50°C, and the freezing rate is 10°C / min.
[0081] The preparation method of the polymer-modified bentonite of the present embodiment is as follows: by weight, 75 parts of bentonite, 5.4 parts of acrylic acid, 4.5 parts of sodium carbonate and 100 parts of water are added into a reaction kettle and stirred at a stirring speed of 200 rpm for 45 minutes, then 0.9 parts of sodium carboxymethyl cellulose is added, and then the solution is heated to 80° C., 3.5 parts of N,N'-methylenebisacrylamide and 0.8 parts of potassium persulfate are added and stirred for 120 minutes to cause a polymerization reaction, after the reaction is completed, the solution is filtered to retain the filter residue, and then the filter residue is washed with deionized water for 3 times, and finally vacuum dried at room temperature to constant weight to obtain the polymer-modified bentonite.
[0082] The soil modification and repair agent of this embodiment is a mixture of phosphate and limestone in a mass ratio of 3:1. The phosphate is iron phosphate. The clay mineral is a mixture of montmorillonite, attapulgite, zeolite and vermiculite in a mass ratio of 4:2:2.5:1.5.
[0083] The preparation method of the soil heavy metal pollution remediation agent based on biomass power plant ash of this embodiment comprises the following steps:
[0084] S1. Pretreatment of biomass power plant ash: The biomass power plant ash is sequentially washed, crushed, dried and sieved to obtain pretreated biomass power plant ash with an average particle size of 500 nm;
[0085] S2. Preparation of surface-modified porous biomass power plant ash: The pretreated biomass power plant ash obtained in S1 is sequentially subjected to liquid nitrogen freezing and freeze drying, followed by grinding and sieving to obtain porous biomass power plant ash clusters, and then the porous biomass power plant ash clusters are surface-modified by γ-aminopropyltriethoxysilane and humic acid to obtain surface-modified porous biomass power plant ash;
[0086] S3. Forming of soil heavy metal pollution remediation agent: Add surface modified porous biomass power plant ash, polymer modified bentonite, soil modification remediation agent and clay mineral into a mixer according to weight proportions, mix evenly, and then form into spherical, cylindrical or rod shapes through a double-roll extrusion granulator. The parameters of the double-roll extrusion granulator are as follows: roller diameter is 300mm; roller speed is 50rpm; extrusion pressure is 50MPa; particle diameter is 10mm; mold aperture is 5mm; power is 22kW, and finally dried through an infrared dryer and packaged for storage.
[0087] Comparative Example 1
[0088] It is basically the same as Example 1, except that an equal amount of pretreated biomass power plant ash is used to replace the porous biomass power plant ash clusters, that is, the pretreated biomass power plant ash is not frozen with liquid nitrogen, freeze-dried, and ground and sieved, so the microstructure is the original morphology and does not contain a herringbone-shaped porous structure.
[0089] Comparative Example 2
[0090] It is basically the same as Example 1, except that the porous biomass power plant ash clusters are not subjected to surface modification treatment.
[0091] Comparative Example 3
[0092] It is basically the same as Example 1, except that the bentonite is not modified by the polymer.
[0093] Comparative Example 4
[0094] It is basically the same as Example 1, except that phosphate and limestone are not added to the soil heavy metal pollution remediation agent.
[0095] Comparative Example 5
[0096] It is basically the same as Example 1, except that no clay mineral is added to the soil heavy metal pollution remediation agent.
[0097] Performance Test:
[0098] The chemical composition of the biomass power plant ash was analyzed using an X-ray fluorescence spectrometer (model: PANalytical Axios, Netherlands, with high material analysis accuracy and suitable for solid samples). The test results are shown in Table 2. The results show that the contents of SiO2 and CaO in the biomass power plant ash are relatively high, at 47.26% and 19.19% respectively.
[0099] Table 2 Chemical composition of biomass power plant ash in Example 1
[0100]
[0101] 3 to 5 days before rice transplanting, 100 kg / mu of soil heavy metal pollution remediation agent was applied to the experimental group, and a control group without the addition of the remediation agent was set up. After the rice was harvested, the soil pH value, effective cadmium / lead content, and cadmium / lead content in rice were tested in accordance with NY / T1377-2007, GB / T23739-2009, and GB5009.15-2014 standards. The determination of soil pH is used to evaluate the effect of soil acidity and alkalinity on the activity of heavy metals; the detection of effective cadmium / lead content analyzes the active state of cadmium and lead in the soil that can be absorbed by plants; at the same time, the effect of soil heavy metal pollution remediation agent in reducing the accumulation of heavy metals in rice was further evaluated by detecting the cadmium / lead content in rice.
[0102] The performance of the control group, examples 1 to 4 and comparative examples 1 to 5 are summarized in Table 3.
[0103] Table 3 Performance of the control group, examples 1 to 4 and comparative examples 1 to 5
[0104]
[0105] The main difference between Comparative Example 1 and Example 1 is that Comparative Example 1 uses equal amounts of pretreated biomass power plant ash to replace the porous biomass power plant ash clusters, and the pretreated biomass power plant ash has not been subjected to liquid nitrogen freezing, freeze drying, grinding and screening, so its microstructure is the original morphology and does not contain a fishbone-shaped porous structure. As can be seen from Table 3, the porous biomass power plant ash clusters of Example 1 can significantly increase the pH value of the soil and reduce the content of effective cadmium and lead in the soil. This is because the fishbone-shaped porous structure significantly increases the specific surface area and adsorption capacity of the material, and can more effectively adsorb and fix heavy metal ions in the soil, reducing their mobility and bioavailability. At the same time, the porous structure of Example 1 also helps to increase rice yield and reduce the cadmium and lead content in rice, further proving the inhibitory effect of the structure on heavy metal pollution during the repair process.
[0106] The main difference between Comparative Example 2 and Example 1 is that the porous biomass power plant ash clusters in Comparative Example 2 have not been subjected to surface modification. As can be seen from Table 3, the porous biomass power plant ash clusters subjected to surface modification in Example 1 can significantly increase the soil pH and reduce the effective cadmium and lead content in the soil. This is because the surface modification treatment can introduce more active adsorption sites and enhance the adsorption capacity of the material for heavy metal ions, thereby more effectively reducing the bioavailability of heavy metals in the soil. In addition, the surface-modified porous biomass power plant ash also significantly reduced the cadmium and lead content in rice and increased rice yield, indicating that the surface modification treatment can more effectively improve the performance of the heavy metal pollution remediation agent.
[0107] The main difference between Comparative Example 3 and Example 1 is that the bentonite in Comparative Example 3 has not been modified with a polymer. As can be seen from Table 3, the bentonite modified with a polymer in Example 1 can significantly reduce the effective cadmium and lead content in the soil and increase the soil pH value. This is because the polymer modification can significantly enhance the adsorption capacity of bentonite for heavy metal ions, especially under acidic conditions, where the polymer can provide additional chelating and adsorption sites to further fix heavy metal ions in the soil. In contrast, the unmodified bentonite has a weaker adsorption capacity for heavy metals, resulting in higher cadmium and lead content in rice and relatively low rice yield.
[0108] The main difference between Comparative Example 4 and Example 1 is that the soil heavy metal pollution remediation agent in Comparative Example 4 does not add phosphate and limestone. As can be seen from Table 3, the heavy metal pollution remediation agent in Example 1 to which phosphate and limestone are added can significantly increase the soil pH value and significantly reduce the effective cadmium and lead content in the soil. This is because phosphate can form insoluble phosphate precipitation with heavy metal ions, thereby reducing the bioavailability of heavy metals, while limestone further reduces the solubility and mobility of heavy metal ions by increasing the pH value of the soil. Therefore, the cadmium and lead content of rice in Example 1 is significantly lower than that in Comparative Example 4, and the rice yield is higher, indicating that the addition of phosphate and limestone plays an important role in the remediation of heavy metal pollution.
[0109] The main difference between Comparative Example 5 and Example 1 is that no clay minerals are added to the soil heavy metal pollution remediation agent in Comparative Example 5. As can be seen from Table 3, the remediation agent in Example 1 with the addition of clay minerals can significantly reduce the effective cadmium and lead content in the soil and increase the soil pH value. This is because clay minerals have a strong adsorption capacity and can effectively fix heavy metal ions in the soil, reducing their mobility and bioavailability. In contrast, in Comparative Example 5 where no clay minerals were added, the effective cadmium and lead content in the soil was higher, the cadmium and lead content in the rice was also higher, and the rice yield was lower, indicating that clay minerals play an important adsorption and fixation role in the remediation of heavy metal pollution.
[0110] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.
Claims
1. A soil heavy metal pollution remediation agent based on biomass power plant ash, characterized in that: The composition comprises the following components in parts by weight: 30 to 45 parts of surface modified porous biomass power plant ash, 4.5 to 9.0 parts of polymer modified bentonite, 3 to 7 parts of soil modification and repair agent, and 1.5 to 4.5 parts of clay mineral; The surface-modified porous biomass power plant ash is prepared from γ-aminopropyltriethoxysilane and humic acid surface-modified porous biomass power plant ash clusters; The porous biomass power plant ash clusters are obtained by freezing the biomass power plant ash with liquid nitrogen, freeze drying, grinding and screening; The polymer modified bentonite is obtained by modifying bentonite through polymerization reaction of acrylic acid and sodium carboxymethyl cellulose monomers; The average diameter of the porous biomass power plant ash clusters is 100 to 200 μm; The specific surface area of the surface modified porous biomass power plant ash is 300 to 500 m 2 / g; The porous structure of the surface modified porous biomass power plant ash is a fishbone structure, and the porous pore spacing is 1.0 to 3.5 μm.
2. The soil heavy metal pollution remediation agent based on biomass power plant ash according to claim 1, characterized in that: The preparation method of the surface modified porous biomass power plant ash is as follows: by weight, 20 to 35 parts of porous biomass power plant ash clusters, 2.0 to 5.0 parts of γ-aminopropyltriethoxysilane, 1.0 to 3.0 parts of humic acid and 100 to 150 parts of ethanol are added into a container, stirred at room temperature at a rotation speed of 200 to 400 rpm for 120 to 360 minutes, then filtered and retained the filter residue, and the filter residue is completely vacuum dried at room temperature to obtain the surface modified porous biomass power plant ash.
3. The soil heavy metal pollution remediation agent based on biomass power plant ash according to claim 2, characterized in that: The preparation method of the porous biomass power plant ash clusters is as follows: in parts by weight, the biomass power plant ash is sequentially washed, crushed, sieved and dried to obtain pretreated biomass power plant ash, 10 to 25 parts of pretreated biomass power plant ash, 1.0 to 2.5 parts of glucose, 2.0 to 5 parts of clay minerals and 100 parts of water are mixed evenly and added to a columnar glass tube, and then vertically immersed in liquid nitrogen for liquid nitrogen freezing, after the ice crystal front converges from the outside to the inside center of the columnar glass tube, it is then completely dried by freeze drying, and then the freeze-dried glucose-biomass power plant ash complex in the columnar glass tube is taken out, and then it is placed in a tubular furnace to be cracked at a temperature of 600 to 800° C. for 120 to 240 minutes under a nitrogen atmosphere, and after cooling to room temperature, the sample is lightly ground and sieved to obtain a porous biomass power plant ash cluster.
4. The soil heavy metal pollution remediation agent based on biomass power plant ash according to claim 1 or 3, characterized in that: The freezing temperature of the liquid nitrogen is -50 to -80°C, and the freezing rate is 6 to 10°C / min.
5. The soil heavy metal pollution remediation agent based on biomass power plant ash according to claim 1, characterized in that: The preparation method of the polymer modified bentonite is as follows: by weight, 50-75 parts of bentonite, 2.4-5.4 parts of acrylic acid, 1.5-4.5 parts of sodium carbonate and 100 parts of water are added into a reaction kettle, stirred at a stirring speed of 100-200 rpm for 30-45 minutes, then 0.4-0.9 parts of sodium carboxymethyl cellulose are added, the solution is then heated to 70-80°C, 1.0-3.5 parts of N,N'-methylenebisacrylamide and 0.2-0.8 parts of potassium persulfate are added, and stirring is continued for 60-120 minutes to cause a polymerization reaction, after the reaction is completed, the solution is filtered to retain the filter residue, and then the filter residue is washed with deionized water for 3 times, and finally vacuum dried at room temperature to constant weight to obtain the polymer modified bentonite.
6. The soil heavy metal pollution remediation agent based on biomass power plant ash according to claim 5, characterized in that: The mass ratio of the acrylic acid to sodium carboxymethyl cellulose is 6:
1.
7. The soil heavy metal pollution remediation agent based on biomass power plant ash according to claim 1, characterized in that: The soil modifying and repairing agent is a mixture of phosphate and limestone in a mass ratio of (2-3):
1.
8. The soil heavy metal pollution remediation agent based on biomass power plant ash according to claim 7, characterized in that: The phosphate is any one of tricalcium phosphate, monocalcium phosphate, dicalcium phosphate or ferric phosphate.
9. The soil heavy metal pollution remediation agent based on biomass power plant ash according to claim 1, characterized in that: The clay mineral is a mixture of montmorillonite, attapulgite, zeolite and vermiculite in a mass ratio of 4:2:2.5:1.
5.
10. The method for preparing the soil heavy metal pollution remediation agent based on biomass power plant ash according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Pretreatment of biomass power plant ash: washing, crushing, drying and sieving the biomass power plant ash in sequence to obtain pretreated biomass power plant ash with an average particle size of 300 to 500 nm; S2. Preparation of surface-modified porous biomass power plant ash: The pretreated biomass power plant ash obtained in S1 is sequentially subjected to liquid nitrogen freezing and freeze drying, followed by grinding and sieving to obtain porous biomass power plant ash clusters, and then the porous biomass power plant ash clusters are surface-modified by γ-aminopropyltriethoxysilane and humic acid to obtain surface-modified porous biomass power plant ash; S3. Forming of soil heavy metal pollution remediation agent: Add surface modified porous biomass power plant ash, polymer modified bentonite, soil modification remediation agent and clay mineral into a mixer according to weight proportions, mix evenly, and then form into any one of spherical, cylindrical or rod shapes through a double-roll extrusion granulator. The parameters of the double-roll extrusion granulator are as follows: roller diameter of 150-300mm; roller speed of 25-50rpm; extrusion pressure of 10-50 MPa; particle diameter of 3-10mm; mold aperture of 0.5-5mm; power of 7.5-22 kilowatts. Finally, dry in an infrared dryer and package for storage.
Citation Information
Patent Citations
Soil conditioner based on biomass power plant ash and preparation method thereof
CN117821078A
Heavy-metal-polluted acidic soil repairing material as well as preparation method and application thereof
CN102329620A
Healing agent of cadmium-polluted water and soil, preparation method and application thereof
CN104690087A
Preparation and application of conditioner capable of repairing heavy metal contaminated soil
CN107739614A
Contaminated soil remediation material preparation method
CN108865152A
Cited By
Modifier for cadmium-polluted soil and preparation method thereof
CN121555203A
An improving agent for cadmium contaminated soil and a preparation method thereof
CN121555203B